The Three Hephthalite Wars of Peroz 474/5-484 - SYVÄNNE, Ilkka (Historia i Świat, 2021)
The first aim of this study is to reconstruct the main features of Peroz’s Hephthalite wars and their military significance for Persia. Secondly, it seeks to analyze the combat doctrine and tactics used by Peroz. Thirdly, the study aims to show what lessons the Persians drew from his defeat and how this affected the Persian combat doctrine. This article demonstrates how the reckless behaviour of Peroz resulted in military, political and economic disasters which undid the achievements of the previous generations. This analysis shows how his disastrous policies led to the abandonment of the reforms of the Bahram V Gur and caused the adoption of one-sided combat doctrine.